Protein recovery from sludge: a review - Xiao, Keke (2022)
Protein recovery from sludge is a simple and well-studied waste-to-resource approach to convert the “wasted” sludge to useful “product”. This article reviews different pretreatment methods to accelerate the release/solubilization of protein from sludge, including physical, thermal, chemical, biological options, and their combinations. Based upon the papers reviewed, protein release/solubilization from sludge was found to be the determining step prior to recovery. The alkaline pretreatment at pH 12 was the most effective method for protein solubilization when compared with ultrasonic (1 W mL−1) and thermal (80 °C) pretreatments, if only considering the released protein concentration. Moreover, pretreatments can change protein properties (e.g., molecular weight, conformation, type, etc.), and the details were summarized. The recovered protein can be alternatives for poultry feedstuff, wood adhesive and fire-extinguishing foam, and its separation from sludge liquor can considerably reduce the nitrogen load to the wastewater treatment plant and the environment. Finally, the integration of circular economy into protein recovery from sludge was proposed, and the related system boundaries for life cycle assessment of this technology were defined. Future research should focus on promoting its full-scale implementation by tackling with the technical, economic, social, and environmental challenges.